2010
DOI: 10.1136/ip.2009.025452
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the population-level impact of tai-chi on falls and fall-related injury among community-dwelling older people

Abstract: Substantial investment in, and high population uptake of, tai-chi would be required to have a large effect on falls and fall-related hospitalisation rates. Although not accounted for in this study, investment in tai-chi is likely to be associated with additional significant health benefits beyond falls prevention. This approach could be applied to other interventions to assist selection of the most cost-effective falls-prevention portfolio for Australia and other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…The power of this Cochrane and other systematic reviews of evidence to directly underpin policy decisions cannot be overstated, yet they are not common in sports medicine. The power of active collaborations with policy makers and investment of research effort in developing realistic cost–benefit estimates for both different preventive actions as well as the costs of inaction have also been demonstrated for falls prevention in older people 3234. Other successful injury prevention information strategies have including the development and validation of injury indicators that could also be used to monitor policy need and success over time 14 15 35…”
Section: Challenges For Better Information Provision To the Public Hementioning
confidence: 99%
“…The power of this Cochrane and other systematic reviews of evidence to directly underpin policy decisions cannot be overstated, yet they are not common in sports medicine. The power of active collaborations with policy makers and investment of research effort in developing realistic cost–benefit estimates for both different preventive actions as well as the costs of inaction have also been demonstrated for falls prevention in older people 3234. Other successful injury prevention information strategies have including the development and validation of injury indicators that could also be used to monitor policy need and success over time 14 15 35…”
Section: Challenges For Better Information Provision To the Public Hementioning
confidence: 99%
“…Exercise is an effective intervention for the prevention of falls; however, some forms of exercises have been shown to be more effective than others, with systematic reviews and meta-analyses finding high-dose exercise, including challenging balance training, the most effective [32,33]. Several Web-based falls-prevention programs have been introduced [34,35]. Some exercise programs, such as the Otago program, have been the focus of Australian nationwide public health strategies to address the issue.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the impressive article in the October 2010 issue by Day and colleagues,1 who found that tai chi can have a large effect on falls and fall-related hospitalisation rates.…”
mentioning
confidence: 99%